Pengembangan Alat Ukur Jarak Berbasis Arduino Nano Dengan Tampilan di LCD Pada Materi Bangun Ruang Sisi Datar - Elin Elin; Sandie Sandie; Nurmaningsih Nurmaningsih (Pusat Riset dan Inovasi Nasional, 2023)
The research method used in this study is the research and development method or also called Research and Development. The research design that will be developed in this study uses the development model presented by Borgan Gall. The product produced in this study is an Arduino Nano-Based Distance Measuring Tool with a Display on the LCD on the Flat Side Room Building Material for Class VIII at SMP Negeri 5 Sepauk. The test subjects of this study included two subjects. The first subject is the validator and the second is class VIII students of SMP Negeri 5 Sepauk. The analysis technique used is to determine the effectiveness, practicality, and validity. The percentage of effectiveness from the average of the two analyzes obtained a percentage value of 94.06% with Very Effective criteria used in learning mathematics. The results of the combined teacher and student response questionnaires - the average percentage obtained was 89.55% with very practical criteria. The combined results of the average percentage obtained from the percentage of experts and the results of the measurement trials obtained a percentage of 76,36% with very valid criteria.